In Vivo Tracking of Mesenchymal Stem Cell in Rat Genitalia with Erectile Dysfunction Labeled by Superparamagnetic Iron Oxide Using Magnetic Resonance Imaging and Its Therapeutic Effect - Taek Oh, Kyung; Ha Hoang, Ngoc; Park, So-Young; Seong Lee, Eun; Hwan Kim, Jang; Taik Oh, Young (Iranian journal of radiology, 2018)
Background: Molecular imaging with nanoparticles makes non-invasive monitoring of target cells without sacrifice of subjects and repeated evaluation possible. Objectives: To evaluate the imaging feasibility of a rat animal model with erectile dysfunction (ED) by bilateral cavernosal nerve injury using human mesenchymal stem cells (MSCs) labeled with superparamagnetic iron oxide (SPIO) and simultaneously to evaluate the beneficial effect of MSCs on ED. Materials and Methods: Thirty-six rats were injected with MSCs labeled with SPIO particle into the corpus cavernosum after bilateral cavernosal nerve injury. In vivo MR imaging was serially performed up to 16 weeks using 1.5 T clinical scanner. After MR imaging, the penile specimens were evaluated for the expression of transforming growth factor-β1 (TGF-β1) by polymerase chain reaction. Results: MR imaging showed a drop in signal intensity at the injection site in the stem cell-injected group. The size of hypointensity was decreased in MSC-injected group in a time-dependent manner; whereas, signal void was not detected at the injection site in the control group. In addition, polymeric chain reaction (PCR) analyses of penile tissues from both groups revealed that the mRNA expression of TGF-β1 was significantly decreased in MSC-injected groups after 4 weeks of injection compared to the control group. Conclusion: MSCs’ beneficial effects on ED was monitored with MR imaging, which might be a valuable tool for tracking and therapeutic monitoring in the future clinical study of stem cell therapy in ED.